O25 Evaluation of the ipatient project – a differential diagnosis teaching tool for optometry students. (3rd November 2019) - McClelland, Julie; Beggs, Richard; Jaffrey, Andy; McShane, Niall; Keenan, Shane; Thomson, Clare
Abstract : Introduction: In recent years, an increase in the number of available postgraduate qualifications for Optometrists has facilitated an expansion in the Optometrist's scope of practice allowing management and treatment of a wide range of conditions (Needle et al 2008). It is essential that Optometry teaching both at undergraduate and postgraduate levels involves encouraging the development of clinical decision making based on signs and symptoms that patients present with. Many postgraduate programmes or continuing professional development (cpd) courses available to Optometrists include an element of online learning (Acosta et al 2018). Methods: We developed a novel online simulation tool (iPatient) to afford students opportunities to practice their diagnostic skills on patients presenting with signs and symptoms that typically present as a 'Red Eye'. The iPatient tool simulates patients, randomly generated from a pool of 14 conditions which typically present with a 'Red Eye'. These include conditions that range from mild (e.g. allergic conjunctivitis) to sight-threatening (e.g. acute angle closure glaucoma). Medical notes, level of vision, and ocular measurements are generated to provide a variety of information for each condition. Presenting signs and symptoms directly relate to The College of Optometrists' Clinical Management Guidelines for each of the 14 conditions (College of Optometrists). Following appropriate ethical approval, the application was piloted with a group of undergraduate (n=20) and postgraduate/qualified (n=10) Optometrists. The programme was demonstrated and participants were asked to complete one scenario. Feedback was invited in the form of a structured questionnaire incorporating Likert responses and free comments. Results: Overall positive responses were received from both cohorts supporting the statements that the tool was 'easy to use' and that they 'learnt from the tool'. Results also demonstrated that the tool was 'ready to use in a teaching capacity'. Comments relating to how the programme could be improved included; increasing the number of conditions, improving image quality, reducing background music and refining the design aspect of the programme. Discussion: The suggested improvements could widen the application of the programme within both face-to-face and online undergraduate and postgraduate Optometry courses. In addition to developing Optometrists' skills in a safe simulated environment, this innovative iPatient project has potential to be employed with other healthcare professionals such as nurses and pharmacists. Conclusion: With minor amendments to the programme following the review, this tool has the potential to transform Optometry education and introduce a strong interactive element to teaching. References: Acosta ML, Sisley A, Ross J, Brailsford I, Bhargava A, Jacobs R, Anstice N. Student acceptance of e-learning methods in the laboratory class in Optometry. PLoS One . 2018 Dec 13;13(12):e0209004. doi: 10.1371/journal.pone.0209004. eCollection 2018. College of Optometrists: Clinical Management Guidelines https://www.college-optometrists.org/guidance/clinical-management-guidelines.html Needle JJ, Petchey R, Lawrenson JG. A survey of the scope of therapeutic practice by UK optometrists and their attitudes to an extended prescribing role. Ophthalmic Physiol Opt. 2008 May;28(3):193–203. doi: 10.1111/j.1475-1313.2008.00551.x.